2012
DOI: 10.1590/s1415-47572012005000077
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome system ZZ/ZW in Apareiodon hasemani Eigenmann, 1916 (Characiformes, Parodontidae) and a derived chromosomal region

Abstract: Parodontidae fish show few morphological characteristics for the identification of their representatives and chromosomal analyses have provided reliable features for determining the interrelationships in this family. In this study, the chromosomes of Apareiodon hasemani from the São Francisco River basin, Brazil, were analyzed and showed a karyotype with 2n = 54 meta/submetacentric chromosomes, and a ZZ/ZW sex chromosome system. The study revealed active NORs located on pair 11 and additional 18S rDNA sites on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The family Parodontidae has been used in studies of sex chromosome differentiation, investigating the invasion of repetitive sequences and the increase in W chromosome size [Centofante et al, 2002;Rosa et al, 2006;Vicari et al, 2006;Bellafronte et al, 2009Bellafronte et al, , 2011Bellafronte et al, , 2012Schemberger et al, , 2014. In this study, in situ localization of the (GATA)n sequence revealed the accumulation of this microsatellite in proto-sex and sex chromosomes of 7 species: A. hasemani , A. ibitiensis , Apareiodon sp., P. hilarii , A. affinis , P. cf.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The family Parodontidae has been used in studies of sex chromosome differentiation, investigating the invasion of repetitive sequences and the increase in W chromosome size [Centofante et al, 2002;Rosa et al, 2006;Vicari et al, 2006;Bellafronte et al, 2009Bellafronte et al, , 2011Bellafronte et al, , 2012Schemberger et al, , 2014. In this study, in situ localization of the (GATA)n sequence revealed the accumulation of this microsatellite in proto-sex and sex chromosomes of 7 species: A. hasemani , A. ibitiensis , Apareiodon sp., P. hilarii , A. affinis , P. cf.…”
Section: Discussionmentioning
confidence: 59%
“…and P. hilarii showed the ZZ/ZW heteromorphic system, while A. affinis presents the ZZ/ZW 1 W 2 system ( figs. 1 , 2 ) Bellafronte et al, 2012].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Cytogenetic studies reported a conserved diploid number of 54 chromosomes in Parodontidae with distinctive karyotype formulae and numerical/position variation of 18S and 5S rDNA sites. [16][17][18][19][20][21] In this group, two probes for repetitive DNAs have been described: pPh2004 16 and WAp, 17 isolated by genomic digestion and chromosome microdissection, respectively. In addition, this Neotropical fish group is interesting for genetics studies because there are species without heteromorphic sex chromosomes, species with protosex chromosomes, species with a ZZ/ZW sex chromosome system, and species with a multiple ZZ/ZW 1 W 2 sex chromosome system.…”
mentioning
confidence: 99%
“…In addition, this Neotropical fish group is interesting for genetics studies because there are species without heteromorphic sex chromosomes, species with protosex chromosomes, species with a ZZ/ZW sex chromosome system, and species with a multiple ZZ/ZW 1 W 2 sex chromosome system. [17][18][19][20][21] Furthermore, researchers have proposed that in Parodontidae the spreading of the repeat elements is the major event leading to genome rearrangements. [17][18][19] Thus, in this study, we isolated and characterized several classes of repetitive DNAs to gain a greater understanding of the dynamics of these genomic sequences in karyotypes and of the mechanism of W sex chromosome differentiation in Parodontidae.…”
mentioning
confidence: 99%